PEMBANGUNAN JIWA KEWIRAUSAHAAN DALAM KEPEMIMPINAN PENDIDIKAN BERBASIS AGAMA, FILSAFAT, PSIKOLOGI DAN SOSIOLOGI - Nur Nida Karimah; Zaini Najih Karimi; Muhammad Al Mighwar; Ujang Nurjaman (al-Afkar, Journal For Islamic Studies, 2022)
This study aims to describe and analyze what, why, and how the development of an entrepreneurial spirit in leadership based on religion, philosophy, psychology, and sociology. In this study it was found that the development of an entrepreneurial spirit in educational leadership is the maximum effort of educational leaders to develop entrepreneurial talent for educational stakeholders which by: (1) based on religion means being guided by God's teachings which command humans to have noble entrepreneurial spirits, by scattering on earth, seeking sustenance. lawful, and remembering Allah; (2) based on philosophy means being guided by knowledge and inquiry with reason that requires material fulfillment, which is built with causality, complexity, and realistic thinking; (3) based on psychology means guided by functional psychology, by entrepreneurial practice, entrepreneurial awareness, and observation of entrepreneurial behavior; and (4) based on sociology means being guided by social science that requires independence, by independent investment, not dependence on foreign investment